Revision of the Genus Paracloeodes (Ephemeroptera: Baetidae) in South America - Nieto, Carolina; Salles, Frederico F. (Zootaxa, 2006)
Six new species of Paracloeodes are described: four from Brazil (P. assu, P. atroari, P. peri and P. waimiri), one from Argentina (P. yuto) and one from Bolivia (P. pacawara), based on nymphs. Three other species from South America: P. binodulus, P. eurybranchus and P. ibicui are revised. A cladistic analysis including most of the South American species of Paracloeodes and the monotypic genus Iguaira is presented. A key for all South American species is included.